LE MASQUE COMIQUE DE L’OPÉRA DANS L’ITALIE DU XVIIIe SIÈCLE - Diana TODEA (Studia Universitatis Babeş-Bolyai. Musica)
The Comic Mask of the Opera in the Italy of the 18th century. Opera performances are characterized in the seventeenth century by heterogeneity which brings together in the musical-drama perspective, both tragic and comic situations. These make the serious scenes to constantly mix with various comic episodes. This approach is maintained until the early eighteenth century, when the former dramma per musica, which aimed to be entertainment for the aristocracy, removes from its librettos the comic element that is found to be irrelevant to the topic and not in accordance with the tragic style. During this period there was emphasised the need for the retrieval of verisimilitude and simplicity which were to be found in the comic opera emerged from the common people. These two trends will mark the final separation between the serious and comic styles that will begin to develop from now on towards two independent types, opera seria and comic opera.